2001
DOI: 10.1002/mrd.1034
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of sea urchin egg lipid rafts and their possible function during fertilization

Abstract: Specialized membrane microdomains called rafts are thought to play a role in many types of cell-cell interactions and signaling. We have investigated the possibility that sea urchin eggs contain these specialized membrane microdomains and if they play a role in signal transduction at fertilization. A low density, TX-100 insoluble membrane fraction, typical of lipid rafts, was isolated by equilibrium gradient centrifugation. This raft fraction contained proteins distinct from cytoskeletal complexes. The fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 85 publications
3
31
0
Order By: Relevance
“…We do not know whether and, if so, how, the sperm factor is anchored to or near the PM but it might be through the association with membrane lipid rafts. It has been shown that lipid rafts function as a signalling scaffold where several cell signalling molecules, including PLCs and Src kinases accumulate (reviewed in Zajchowski and Robbins, 2002) and recent reports have shown that the disruption of these domains perturbs the fertilization signalling pathway in sea urchin and Xenopus eggs (Belton et al, 2001;Sato et al, 2002).…”
Section: Mechanism Of Ca 2+ -Wave Pacemaker Operationmentioning
confidence: 99%
“…We do not know whether and, if so, how, the sperm factor is anchored to or near the PM but it might be through the association with membrane lipid rafts. It has been shown that lipid rafts function as a signalling scaffold where several cell signalling molecules, including PLCs and Src kinases accumulate (reviewed in Zajchowski and Robbins, 2002) and recent reports have shown that the disruption of these domains perturbs the fertilization signalling pathway in sea urchin and Xenopus eggs (Belton et al, 2001;Sato et al, 2002).…”
Section: Mechanism Of Ca 2+ -Wave Pacemaker Operationmentioning
confidence: 99%
“…Originally isolated from mammalian endothelial cells in culture (14), lipid rafts have been identified in three invertebrate species: Drosophila, Dictyostelium, and Strongylocentrotus (2,13,32). The proposed functions for UNC-1 have led us to study whether lipid rafts exist in C. elegans and to determine whether UNC-1 or UNC-8 is present in lipid rafts.…”
mentioning
confidence: 99%
“…In addition, the cholesterol-binding compound methyl-␤-cyclodextrin abolishes sperm-egg interaction and/or subsequent Src activation (31). The functional importance of egg rafts has also been suggested in sea urchin fertilization (34). However, the significance of the structural and functional interaction of rafts with the egg cytoplasm and the involvement of Src-PLC␥ pathway in this interaction remain to be established.…”
mentioning
confidence: 99%